2013
DOI: 10.1371/journal.pone.0080440
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid CB2 Receptors Regulate Central Sensitization and Pain Responses Associated with Osteoarthritis of the Knee Joint

Abstract: Osteoarthritis (OA) of the joint is a prevalent disease accompanied by chronic, debilitating pain. Recent clinical evidence has demonstrated that central sensitization contributes to OA pain. An improved understanding of how OA joint pathology impacts upon the central processing of pain is crucial for the identification of novel analgesic targets/new therapeutic strategies.Inhibitory cannabinoid 2 (CB2) receptors attenuate peripheral immune cell function and modulate central neuro-immune responses in models of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 44 publications
4
57
1
3
Order By: Relevance
“…One key variable in these studies may be age of animals that are used for recording as we have previously reported a marked decrease in GABA release probability between neonatal and adult RVM neurons that is the result of increased endocannabinoid tone in the adult rat RVM (Li et al, 2015). Other laboratories have also observed important differences in the function of the RVM between neonatal and adult rats (Hathway et al, 2009(Hathway et al, , 2012. We focused our studies on adult rats to understand modulation of endocannabinoid signaling in the RVM during persistent inflammation.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…One key variable in these studies may be age of animals that are used for recording as we have previously reported a marked decrease in GABA release probability between neonatal and adult RVM neurons that is the result of increased endocannabinoid tone in the adult rat RVM (Li et al, 2015). Other laboratories have also observed important differences in the function of the RVM between neonatal and adult rats (Hathway et al, 2009(Hathway et al, , 2012. We focused our studies on adult rats to understand modulation of endocannabinoid signaling in the RVM during persistent inflammation.…”
Section: Discussionmentioning
confidence: 95%
“…The analysis of tissue endocannabinoids was developed adapting methods previously described (Richardson et al, 2007;Chen et al, 2009;Zhang et al, 2010). Briefly, RVM slices were weighed and placed into 13 Ï« 100 mm screw-top silanized glass tubes, and 100 l of 0.02% trifluoroacetic acid was added.…”
Section: Liquid Chromatography-mass Spectrometry Analysis Of Endocannmentioning
confidence: 99%
See 2 more Smart Citations
“…The tonic release of spinal endocannabinoid levels counteract peripheral sensitization through enhanced endocannabinoid signaling within the spinal cord (42). In a rat model of OA pain, systemic administration of CB2 agonist, JWH-133, suppressed pain behavior, while acute administration to the spine inhibited mechanically stimulated noxious neurotransmission (43).…”
Section: Changes In Cb Receptor Expressionmentioning
confidence: 99%